Managing anti‐epileptic drug treatment in adult patients with intellectual disability: a serious conundrum. (23rd April 2016) - Doran, Z.; Shankar, R.; Keezer, M. R.; Dale, C.; McLean, B.; Kerr, M. P.; Devapriam, J.; Craig, J.; Sander, J. W.
Abstract : Background and purpose: About a quarter of people with epilepsy have intellectual disability (ID). This group has communication issues, premature mortality, more treatment resistance, difficulties in making informed choices and greater risks of physical and mental health comorbidities. There is no specific prescribing guidance for this large and vulnerable group. The literature on prescribing for epilepsy in this group was reviewed, in particular examining how antiepileptic drugs (AEDs) work regarding their side effect profiles, effects on specific epilepsy syndromes associated with ID and their individual strengths and weaknesses based on the nature and degree of ID. Method: This is a narrative review for which a comprehensive search was conducted to identify evidence for prescribing commonly used AEDs to people with ID including genetic syndromes specifically associated with epilepsy. Results: A detailed analysis of the results has highlighted the urgent requirement for suitable and reliable evidence in AED prescribing amongst adults with epilepsy and ID as no studies taking account of the response to AEDs of the ID populations based on the WHO Diagnostic and Statistical Manual of Mental Disorders criteria of clinical severity of ID were identified. Conclusion: There is a significant shortfall in suitably powered studies to provide sufficient evidence for safe prescribing of AEDs to people with ID. Abstract : Clickhere to view the accompanying paper in this issue.